DAMPAK PEMBANGUNAN LRT TERHADAP PERUBAHAN HARGA LAHAN DI KAWASAN TOD CIKUNIR I KOTA BEKASI - Setiacahyanti, Zahra Octavia; Swasto, Deva Fosterharoldas (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
Transportation infrastructure development, such as Light Rail Transit (LRT), has a significant impact on land price changes in surrounding areas. This study aims to analyze changes in residential land market prices before and after the development of the LRT in the Transit-Oriented Development (TOD) area of Cikunir I LRT Station, Bekasi. This research employs a mixed-methods approach with a concurrent design, in which quantitative and qualitative data are integrated for comprehensive analysis. Quantitative data were collected through a survey of 150 respondents, while qualitative data were obtained through interviews with seven stakeholders. Data analysis utilized Kriging interpolation to map the spatial distribution of land prices. The results indicate that residential land market prices in Jatibening increased by an average of up to 106% after the LRT development, with the highest price reaching IDR 16,000,000 per square meter. Areas with the highest land prices are concentrated around the LRT station and main roads, driven by improved accessibility and connectivity. A comparison between NJOP (Tax Object Sales Value), ZNT (Land Value Zone), and market prices shows that market prices better reflect actual dynamics. This study highlights the importance of TOD-based spatial planning to maximize the economic benefits of transportation infrastructure development.